Lattice Boltzmann Method for Thermocapillary Flows (Advances in Applied Mathematics and Mechanics, 2021)
In this paper, we apply a recently proposed thermal axisymmetriclattice Boltzmann model to the thermocapillary driven flow in acylindrical container. The temperature profiles and isothermal linesat the free surface with Prandtl (Pr) number fixed at 0.01 andMarangoni (Ma) number varying from 10 to 500 are measured andcompared with the previous numerical results. In addition, we alsogive the numerical results for different Ma numbers at Pr=1.0. It isshown that present results agree well with those reported inprevious studies.